2012
DOI: 10.1063/1.4745014
|View full text |Cite
|
Sign up to set email alerts
|

Origin of high-temperature relaxor-like behavior in CaCu3Ti4O12

Abstract: The relaxor-like behavior in CaCu3Ti4O12 was investigated in details. The dielectric anomaly was found to be an extrinsic phenomenon related to oxygen vacancy. Annealing treatments in N2 and O2 atmospheres revealed that the relaxor-like behavior is composed of two types of relaxations with close relaxation parameters. Impedance analysis showed that the relaxations appearing in the low- and high-temperature wings of the anomaly are related to the dipolar and Maxwell-Wagner (MW) relaxation, respectively. Both re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 48 publications
4
45
0
Order By: Relevance
“…Furthermore, such a model has also been discussed briefly by Loidl et al 40 Besides, it is known that oxygen vacancies have a significant contribution to the electric/dielectric properties of materials, especially to the high-temperature dielectric anomaly because oxygen vacancies make the ceramics more conductive. 11,28,33,[41][42][43] Herein, it is assumed that the broad e 0 peak appearing around 200 C may be linked with the conductivity, and the dielectric behavior should follow the power law [UDR law] 44…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, such a model has also been discussed briefly by Loidl et al 40 Besides, it is known that oxygen vacancies have a significant contribution to the electric/dielectric properties of materials, especially to the high-temperature dielectric anomaly because oxygen vacancies make the ceramics more conductive. 11,28,33,[41][42][43] Herein, it is assumed that the broad e 0 peak appearing around 200 C may be linked with the conductivity, and the dielectric behavior should follow the power law [UDR law] 44…”
Section: Resultsmentioning
confidence: 99%
“…This behavior was ascribed to be caused by charge ordering known as electronic ferroelectricity . Our recent work revealed that this relaxor behavior is an extrinsic phenomenon related to oxygen vacancies . This behavior is now called pseudo‐relaxor behavior, which is composed of two close relaxations with the low‐temperature one being a dipolar relaxation and the high‐temperature one being a Maxwell‐Wagner relaxation …”
Section: Introductionmentioning
confidence: 99%
“…Annealing treatment in reducing and/or oxidizing ambient has been proved to be an effective way to identify whether the relaxation is related to a bulk or an interfacial effect [16,17]. Figure 4b shows the comparison of the dielectric anomaly before and after oxidation treatment in oxygen atmosphere at 1000°C for 10 h. For peak A, the obvious peak of the as-sintered sample was slightly depressed, indicating that the annealing treatment had no significant influence on the dielectric anomaly.…”
Section: Resultsmentioning
confidence: 94%